Women’s Ijtihad and Lady Amin’s Islamic Ethics on Womanhood and Motherhood - Ladan Rahbari (Religions, 2020)
Women’s position, identity, and value in Islam have been affected by androcentric interpretations of the Qur’an and hadith throughout Islamic history. Women’s roles in society, as well as their position vis-à-vis Islamic sources and authority, have been shaped by these interpretations. In Shi’a Islam, due to the majority male clergy’s resistance, women have rarely reached the highest loci of Shi’i authority and jurisprudence. However, there have been women scholars who have transgressed these normative frameworks. Lady Amin, who was one of the most prominent Iranian theologians of the 19th and 20th centuries, is a notable example. Lady Amin had great knowledge of jurisprudence and gained the status of mujtahida at the age of forty. Her scholarly work addressed not only interpretations of the Qur’an and hadith, but also women’s issues and gender politics of her time. This study addresses women’s ijtihad in Shi’a Islam and investigates Lady Amin’s teachings on the topics of womanhood and motherhood. This study focuses on Lady Amin’s book of Islamic ethics, titled Ways of Happiness: Suggestions for Faithful Sisters, written as a Shi’i source of guidance with a specific focus on women and gender in Shi’a Islam.